2021
DOI: 10.3390/jcm10163459
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stress and Masticatory Muscle Activity in Female Students

Abstract: The aim of the study was to analyze the relationship between stress measured by the perceived stress scale (PSS-10) questionnaire and masticatory muscle activity. Experimental design assumed the study of healthy young women without temporomandibular disorders, dividing them into three groups depending on the result of the stress level and then comparing these groups in terms of bioelectrical activity of the masticatory muscles. After the exclusion criteria were applied, 63 female students (mean age: 22.3 ± 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…This result is consistent with other studies that demonstrated significant associations between stress, anxiety, depression, and TMDs [26,27]. Higher levels of stress and depression are related to changes in electrical potentials and asymmetry of the masticatory muscles during clenching [28,29]. In fact, higher levels of masticatory muscle pain perception were demonstrated in response to psychological stress in Sprague-Dawley rats [30].…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with other studies that demonstrated significant associations between stress, anxiety, depression, and TMDs [26,27]. Higher levels of stress and depression are related to changes in electrical potentials and asymmetry of the masticatory muscles during clenching [28,29]. In fact, higher levels of masticatory muscle pain perception were demonstrated in response to psychological stress in Sprague-Dawley rats [30].…”
Section: Discussionsupporting
confidence: 92%
“…The sEMG protocol was tested by dual sEMG measurements on 10 participants. These two independent sEMG measurements were separated by 5 min of rest between activities [23]. There were no significant differences between repeated sEMG recordings in all variables analyzed in the mandibular resting position.…”
Section: Study Protocol 221 Assessment Of the Muscle Activitymentioning
confidence: 99%
“…The sEMG protocol was tested by dual sEMG measurements on 10 participants. This two independent sEMG measurements were separated by 5 min of rest between activities 30 . There were no significant differences between repeated sEMG recordings in all functions analyzed (maximal clenching, maximal roller clenching, and maximal mouth opening).…”
Section: Experiments Designmentioning
confidence: 99%